Palaeoclimate within the river Rhine catchment during Holocene and historic times - Glaser, Rüdiger; Ammann, Brigitta; Brauer, Achim; Heiri, Oliver; Jacobeit, Jucundus; Lotter, André F.; Luterbach, Jürg; Maisch, Max; Magny, Michel; Pfister, Christian; Tinner, Willy; Veit, Heinz; et al. (ERDKUNDE, 2005)
The present article summarizes the state of the art knowledge concerning climatic fluctuations in the Rhine catchment area on different time scales and spatial resolution. The first part deals with the results focussed on the alpine and Hochrhein area, which can due to its elevation and specific geoecological setting regarded as especially sensitive to climatic fluctuations. The basis is a broad variety of palaeoclimatic indicators, by which the climate development during the postglacial and Holocene period can be analysed. In addition, results for the middle Rhine area, derived from Eifel maar varves are discussed. These data exhibit a yearly resolution. The second part is based on chronological readings, giving evidence about the climate since AD 1000 in detail. Beside the overall temperature and precipitation development, these data also include information about climatic extremes, likewise flood events. For some tributaries likewise the Main River and the lower Rhine area there significant changes and fluctuations through time. In addition it was possible to derive out of European wide historical data sets pressure grid sets, enabling the derivation of circulation patterns.